2017
DOI: 10.1002/pon.4479
|View full text |Cite
|
Sign up to set email alerts
|

Sexual life after mastectomy in breast cancer survivors: A qualitative study

Abstract: It was found that in Iranian society, due to cultural context, some taboos, and patriarchal structure, the patients are placed under added pressure following mastectomy. As a consequence, they suffer emotional problems, in addition to physical complications of the disease and its treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
(50 reference statements)
0
26
0
5
Order By: Relevance
“…It seems that in Iranian society, for cultural reasons, women are placed under additional pressure following the diagnosis and treatment of BC. As a result, while suffering from physical complications of the disease and its treatment, BC patients suffer from stress and emotional problems [49]. The higher prevalence of depression among BC survivors in Iran can be explained as the result of lack of support from society and patients’ families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that in Iranian society, for cultural reasons, women are placed under additional pressure following the diagnosis and treatment of BC. As a result, while suffering from physical complications of the disease and its treatment, BC patients suffer from stress and emotional problems [49]. The higher prevalence of depression among BC survivors in Iran can be explained as the result of lack of support from society and patients’ families.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, psychological problems and sexual dysfunction after BC treatment have been reported in the majority of patients [51,52]. For example, a study of Iranian patients suggested that after treatment (i.e., mastectomy), women had negative feelings about their bodies [49]. It has also been suggested that when Iranian women with BC are about to engage in sexual intercourse, they face anxiety, shame, and negative feelings about their bodies [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because talking about sexual issues is a matter of great cultural sensitivity and is considered as a cultural taboo in Iran. 43 Also, sexual history taking is not routinely performed by clinicians. 41 Thus, nurses and clinicians need to learn the communication skills to discuss about patients’ sexual problems.…”
Section: Discussionmentioning
confidence: 99%
“…Estos revelan problemas de tipo sentimental, y sexual, a partir del tratamiento, en especial en mujeres mastectomizadas, o en el caso del cáncer de cuello uterino por la estigmatización que tiene la enfermedad al estar asociada al contagio del Virus del Papiloma Humano (21,22) . En este estudio, los problemas con la pareja se acentúan por la dinámica de las relaciones familiares y la migración de las mujeres.…”
Section: Discussionunclassified